A Qualitative Study of Malaysian Parents' Purchase Intention of Functional Weaning Foods using the Theory of Planned Behavior. Issue 2 (12th February 2019) - Mohamad, Hajar; Mirosa, Miranda; Bremer, Phil; Oey, Indrawati
ABSTRACT: Background : In this study, qualitative research methods were used to explore the behavioral, normative, and control beliefs underpinning parents' decisions to purchase functional weaning food products. Methods : Seven focus groups were conducted with 44 parents in two locations in Malaysia (Sabah and Selangor). Based on the Theory of Planned Behavior theoretical framework, participants were prompted with questions about commercial weaning foods including functional weaning foods and shown several different products to stimulate discussion. Results : Important behavioral beliefs (product attributes, babies' needs and suitability of the product, perceived healthiness), referrals and influences (family and friends' opinions and experiences, internet and social media influence, health professionals' recommendation and advice) and facilitating and inhibiting factors (trust and confidence, brand and cost, and product availability and options) were identified. Conclusions : Overall functional weaning food purchase intention was influenced positively and negatively by behavioral, normative and control beliefs. To increase the awareness and commercial product knowledge on weaning food are suitable for their children, more information on functional weaning food products from reliable sources that can reach the parents and other potential customers is needed. Government, health professionals and manufacturers should work together to develop a better way to inform parents about functional weaning foods.